The complete mitochondrial genome of Apatura laverna (lepidoptera: Nymphalidae) - Ju-Ping Wang; Yun-Fei Peng; Ping Gao; Tian-Wen Cao (Mitochondrial DNA. Part B. Resources, 2021)
Apatura laverna is subordinate to Apatura Fabricius of Nymphalidae, and endemic to China. The complete mitochondrial genome of A. laverna was sequenced and analyzed in the study. The length of the complete mitogenome is 15,187 bp, including 37 genes and a control region. COI gene initiate with a CGA codon, the rest 12 genes start with typical ATN. Eleven of 13 PCGs have a complete stop codon TAN except for COII and ND4 have a single T. The phylogenetic analyses support that A. laverna has a close relationship with the clade including A. metis and A. ilia.